2017
DOI: 10.1007/s00128-017-2117-3
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Pesticides Residues in Human Breast Milk from the Middle Governorates in Jordan in 2013/2014

Abstract: One hundred samples of mother breast milk were gathered from six middle governorates and districts in Jordan in 2013/2014 to monitor Organochlorine pesticides pollutants. The results showed clearly that banned organochlorine pesticides are still detected in the monitored samples in low concentration despite banning of these persistent pollutants in Jordan since 36 years ago. However, the results indicated that 1% of the contaminated samples contained β-HCH, 5% γ-HCH, 3% p,p'-DDD, 2% heptachlor, 45% p,p'-DDE an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…2015 ), several brominated flame retardants (BFRs) ( Antignac et al. 2016 ), organochlorine pesticides (OCPs) ( Al Antary et al. 2017 ; Polanco Rodríguez et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2015 ), several brominated flame retardants (BFRs) ( Antignac et al. 2016 ), organochlorine pesticides (OCPs) ( Al Antary et al. 2017 ; Polanco Rodríguez et al.…”
Section: Introductionmentioning
confidence: 99%
“…Human milk presents a noninvasive way to monitor POPs levels in the population and is preferable to blood serum for the detection of lipophilic compounds owing to its higher lipid content. Recent studies have reported on the occurrence of PCBs (Mamontova et al 2017;Müller et al 2017;Bawa et al 2018) and polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) (Abballe et al 2008;Fång et al 2015), several brominated flame retardants (BFRs) (Antignac et al 2016), organochlorine pesticides (OCPs) (Al Antary et al 2017;Polanco Rodríguez et al 2017;Bawa et al 2018;Chen et al 2018), and CPs (Cao et al 2017;Xia et al 2017aXia et al , 2017bYang et al 2018) in human milk. However, the small sample sizes of many studies and high variability due to individual differences between participating mothers hinder comparisons and the evaluation of results from different countries.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, three studies did not discover any associations between parity and POPs level in human specimens. However, the absence of associations in the first study was not statistically tested (6). The second study did not discover any significant correlations between parity and POPs levels in breast milk.…”
Section: Paritymentioning
confidence: 74%
“…Although dietary habit is an important risk factor affecting POPs levels in human specimens, some studies did not discover correlations between these two variables. A study from Jordan stated that there were no associations between dietary habits and POPs levels in the breast milk of 100 mothers, but there was a high probability that they were not statistically tested (6). A study conducted in China also failed to discover a significant correlation between dietary habits and OCPs concentration in human milk, with the varying sources of OCPs and not only from a particular source was cited as the probable cause (39).…”
Section: Dietary Habitsmentioning
confidence: 99%
See 1 more Smart Citation